2004
DOI: 10.1016/j.jmb.2003.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Catalytic Domain of MMP-16/MT3-MMP: Characterization of MT-MMP Specific Features

Abstract: Membrane-type matrix metalloproteinases (MT-MMPs) have attracted strong attention, because four of them can activate a key player in the tumor scenario, proMMP-2/progelatinase A. In addition to this indirect effect on the cellular environment, these MT-MMPs degrade extracellular matrix proteins, and their overproduction is associated with tumor growth. We have solved the structure of the catalytic domain (cd) of MT3-MMP/MMP-16 in complex with the hydroxamic acid inhibitor batimastat. CdMT3-MMP exhibits a class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 66 publications
2
35
0
1
Order By: Relevance
“…TIMP-1 binds most active forms of MMPs, the exceptions being MMP-14 and MMP-16 (Brew et al, 2000;Lang et al, 2004). Following incubation of RCC-53 with 700 ng/ml of TIMP-1-GPI protein for 24 h, FACS analyses using MMP-1, MMP-2, MMP-3, specific antibodies showed, with the exception of MMP-14, an increase in mean channel fluorescence intensity (MFI) for each of the MMPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TIMP-1 binds most active forms of MMPs, the exceptions being MMP-14 and MMP-16 (Brew et al, 2000;Lang et al, 2004). Following incubation of RCC-53 with 700 ng/ml of TIMP-1-GPI protein for 24 h, FACS analyses using MMP-1, MMP-2, MMP-3, specific antibodies showed, with the exception of MMP-14, an increase in mean channel fluorescence intensity (MFI) for each of the MMPs.…”
Section: Resultsmentioning
confidence: 99%
“…While not much is known about TIMP-1 association with MMP-15, binding of TIMP-1-GPI protein to MMP-16 would not be predicted to occur based on the rather poor avidity of native TIMP-1 for this protein (Lang et al, 2004). However, recent structural studies have identified the amino acids that apparently explain this low association reaction/affinity (Lang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recombinant catalytic domain of MT1-MMP(cMTl), MT3-MMP(cMT3) and pro-MMP-2 were produced in Liège (Lang et al, 2004). Pro-MMP-9 was purchased from R&D Systems.…”
Section: Enzymesmentioning
confidence: 99%